Factors Influencing the Level of Benefits Derived from Social Group Participation: A Study in Eastern Wollega Zone, Oromia, Ethiopia - Getahun, Gemechu; Chotai, Nila (Society & Sustainability, 2022)
This research empirically examined factors influencing the level of benefits derived from social group membership in Eastern Wollega Zone, Ethiopia. Methodologically the study used an explanatory research design. Quantitative data were gathered from 490 rural households of the Agricultural Growth Program (AGP) targeted districts using a multi-stage sampling technique. Multiple imputation techniques are used to deal with missed observations. An ordered logistic regression model is employed to empirically evaluate the predictors of the level of benefits derived from social group membership. The econometric results of an ordered logistic regression identified nine explanatory variables as factors influencing the benefits derived from the social group. The significant variables were marital status (p<0.05), education (p<0.05), farming status (p<0.01), mixed farming (p<0.01), livestock production (p<0.01), status in membership (p<0.01), trust index (p<0.01), decision making index (p<0.05) and labor contribution index (p<0.05). However, most of the explanatory variables were insignificant i.e. crop production, age, gender, farm size, heterogeneity index, diversity of membership index, cash meeting attendance index, and cash contribution index (not significant at less than 5% but significant at 10%) This study is very important in contributing to scarce literature related to the factors contributing to the level of benefits derived from social group participation in Ethiopia. The results are expected to support decision-makers at the local level, federal government higher ministries, and policymakers by providing empirical evidence on the factors affecting the level of benefits derived from social group participation.